Does the “state of disaster” response have a downside? Hospital incident command group leaders’ experiences of a terrorist-induced major incident: a qualitative study - Jason P. Murphy; Anna Hörberg; Monica Rådestad RN; Lisa Kurland; Maria Jirwe (BMC Emergency Medicine)
Abstract Aim This study explores HICGs’ experience of disaster response during a terrorist-induced major incident major incident. Design A qualitative descriptive design with individual semi-structured interviews was used. Methods This was a qualitative study based on seven individual interviews. Participants were members of hospital incident command groups during a terror attack. The interviews were transcribed verbatim and analyzed using deductive content analysis. The SRQR checklist was used to report the findings. Results The data created from the interviews identified barriers and facilitators for hospital response as well as aligned with previously established categories: Expectations, prior experience, and uncertainty affect hospital incident command group response during a Major Incident and three categories, (I) Gaining situational awareness (containing two subcategories), (II) Transitioning to management (containing three subcategories) and (III) Experiences of hospital incident command group response (containing two subcategories). In addition, the results suggest that an exaggerated response may have led to unanticipated adverse events. Clinical trial number Not applicable.